Diversity of helminth parasites of eight siluriform fishes from the Aguapeí River, upper Paraná basin, São Paulo state, Brazil - Acosta, Aline A. [UNESP]; Smit, Nico J.; da Silva, Reinaldo J. [UNESP] (Elsevier, 2020)
Fishes of the order Siluriformes, known as catfishes, have a global distribution with more than 3,600 valid species of which 2,087 occur in the Neotropical region. Despite being highly diverse, abundant, and of economic importance as food and ornamental fishes, knowledge about the diversity and distribution of their helminth parasites is fragmentary and scarce. Eight species of catfishes (Pterodoras granulosus, Trachydoras paraguayensis, Pimelodella avanhandavae, Loricariichthys platymetopon, Pterygoplichthys ambrosettii, Rhinelepis aspera, Hemisorubim platyrhynchos, and Sorubim lima) from the Aguapeí River, Upper Paraná River basin, municipality of Castilho, São Paulo State, Brazil, were surveyed for helminth parasites. Collected fishes were weighed, measured, and examined for helminth parasites following standard methodology. Fifty helminth parasite taxa (23 monogeneans, 13 digeneans, 11 nematodes, and three cestodes) were found from a total of 405 fishes screened. The helminth taxon that showed the highest mean intensity of infection and mean abundance was the nematode Rondonia rondoni from P. granulosus, followed by the nematode Parasynodontisia petterae from R. aspera. The ecological analyses were carried out at the component community level and at the infracommunity level. Trachydoras paraguayensis had the richest helminth component community. Pterygoplichthys ambrosettii had the most diverse helminth component community and R. aspera had the lowest. Both hosts are loricariids and have similar diet. However, the high parasite diversity of P. ambrosettii is due to the number of dactylogyrids species found (10), which are directly transmitted, whereas only three dactylogyrid species were found in R. aspera. At infracommunity level, the nematode species R. rondoni and P. petterae dominated the parasite communities. This study presents 38 new host records, contributing considerably to increase the diffuse knowledge of helminth parasites of Neotropical siluriforms.
Keywords: Catfishes; Helminthological survey; Neotropical region; Parasite diversity